CO-INFECTION WITH BABESIA CANIS AND BORRELIA BURGDORFERI S.L. IN A DOG FROM NORTHEASTERN ROMANIA: A CASE REPORT - Liviu-Dan MIRON; Lavinia CIUCĂ; Călin ILIE; Andreea POTOROACA; Constantin LAZĂR; Gabriela-Victoria MARTINESCU (Journal of Applied Life Sciences and Environment, 2022)
This study describes a clinical case of a 9-year-old mixed-breed dog co-infected with Babesia canis and Borrelia burgdorferi. This dog was referred to a private clinic in northeastern Romania for a recurrent perianal tumour and a mild inflammation in the right elbow. The dog showed mild haemolytic anaemia, as well as increased alkaline phosphatase and glucose levels. Despite surgery and therapy, after four days, the patient had developed hyperthermia, severe anaemia and an inflammatory syndrome. The blood smear revealed the presence of piroplasm organisms identified as ‘large’ Babesia spp. On the 9th day of hospitalization the patient died during the blood transfusion, before applying the specific therapy for babesiosis. The blood collected before blood transfusion was tested for the following vector-borne diseases: Babesia spp., Anaplasma spp., Ehrlichia spp., Hepatozoon spp. and Borrelia spp. using molecular analysis. The final outcome indicated a co-infection with Babesia canis and Borrelia burgdorferi s.l. In conclusion, the introduction of vector-borne disease screening approach prior any surgical procedure can prevent life-threatening events and improve diagnostic accuracy in dogs infected/co-infected simultaneously with different vector-borne diseases.